Spuścizna niemiecka, kierunek Polski. Zbiór reprodukcji Seminarium Historii Sztuki na Uniwersytecie Poznańskim (1919–1939) - Kłudkiewicz, Kamila (Artium Quaestiones, 2022)
In 1919, the authorities of the newly established University of Poznan took over the buildings and movable property of the German Royal Academy, which had functioned in Poznan between 1903 and 1918. The Seminar of Art History, which was organised at the time, acquired, among other things, a collection of 4,000 slides and 4,000 reproductions which had been used in teaching art history at the German university. Thanks to the first Polish professor of art history, Szczęsny Dettloff, the collection began to grow. Dettloff, one of the fathers of academic art history in Poland, understood perfectly the need to expand the university’s research workshop: the library and the reproduction collection. He built a Polish photo library at the University of Poznan on the basis of the existing German reproduction collection and a set of diapositives acquired in 1919 from the Museum of Wielkopolska (the collection after the German Kaiser Friedrich Museum). The article describes the reproduction collection in the inter-war period, indicates its state of preservation and analyses the role of the local collection in the academic teaching of art history (in the context of the programme of studies, but also of trips for students).